1992
DOI: 10.1089/lps.1992.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Laparoscopic Cholecystectomy

Abstract: An investigation was undertaken to determine whether hospital charges for laparoscopic cholecystectomy are higher than those for traditional open cholecystectomy. Thirty consecutive cases of successfully completed laparoscopic procedures in a single surgeon's experience were compared to 30 open cases performed within the previous calendar year. Patients undergoing open cholecystectomy were excluded if coexisting medical problems or complications prolonged hospitalization beyond 7 days. Mean patient age was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…The majority saw little need for laparoscopic cholecystectomy, perceived a need to wait for prospective outcomes data, or condemned it as a conceptually ''bad'' or ''pointless'' idea. Indeed, early studies seemed to show that laparoscopic cholecystectomy resulted in little patient benefit (besides cosmesis) [7], increased cost to society [8], and had some potential for patient harm [9].…”
Section: Discussionmentioning
confidence: 99%
“…The majority saw little need for laparoscopic cholecystectomy, perceived a need to wait for prospective outcomes data, or condemned it as a conceptually ''bad'' or ''pointless'' idea. Indeed, early studies seemed to show that laparoscopic cholecystectomy resulted in little patient benefit (besides cosmesis) [7], increased cost to society [8], and had some potential for patient harm [9].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic cholecystectomy has been assessed clinically and there are now many studies analyzing the cost benefit of the procedure, particularly in relation to different fractions within the health system [5,18,19,39,43,47]. Likewise, there are a few papers that analyze the costs involved in laparoscopic appendectomy, fundoplication, and herniorrhaphy [4,10,15,29].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed that laparoscopy resulted in little patient benefit, increased cost, and potential harm to patients. 11 The public, however, with help from the lay press and industry, essentially demanded that their surgeons provide this innovative operation. Thus, the rapid dissemination and establishment as the current gold standard was actually driven largely by public demand.…”
mentioning
confidence: 99%